Análisis comparativo de la organización institucional del comercio exterior ecuatoriano: Período Neoliberal (1998-2006) versus período de la Revolución Ciudadana (2007-2016). - Guevara Gallardo, Susana Cristina. (2018)
Foreign trade requires an institutional framework to develop in a stable, predictable way and with a relative control of the risk simplicit in it. Efficient and well-managed Economic and Political institutions are a key factor for the economic development of a country. In the case of foreign trade, its institutionality will be considere defficient if it responds to the internal development needs, if it is adequate to process the requirements of the actors involved in foreign trade activities as well as to fulfill the commitments acquired by the country with international organizations. From this, we can deduce the importance of the study of the institutional organization of foreign trade in the Ecuadorian case. The present thesis work made it possible to carry out a comparative analysis of the institutional organization of foreign trade in Ecuador during two relevant historical phases denominated: Neoliberal period (1998-2006) and period of the Citizen Revolution (2007-2016) under the focus of the theory of the New Institutional Economics (NIE). To do this, this research was initiated by analyzing and comparing the current regulations and the entities –both public and private- that managed the institutionality of foreign trade in Ecuador in both periods. A comparative qualitative analysis of the monetary, exchange and ideological situations prevailing during the two stages under study was also carried out. Finally, a quantitative analysis of the structure of imports and exports of non-oil products was carried out during the aforementioned historical moments. This comparative analysis made it possible to verify that the institutional change simplemented in the transition from neoliberal governments to the government of the citizen revolution were insufficient to change the structure of foreign trade (imports and exports) in Ecuador.